Assessing the Immune Response of Atlantic Salmon (Salmo salar) after the Oral Intake of Alginate-Encapsulated Piscirickettsia salmonis Antigens - Daniela Sotomayor-Gerding; José Miguel Troncoso; Alejandro Pino; Felipe Almendras; Mónica Rubilar Diaz (Vaccines, 2020)
Salmon rickettsial septicaemia (SRS) is the infectious disease that produces the highest losses in the Chilean salmon industry. As a new strategy for the control of SRS outbreaks, in this study we evaluated the effect of alginate-encapsulated Piscirickettsia salmonis antigens (AEPSA) incorporated in the feed as an oral vaccine to induce the immune response in Atlantic salmon (Salmo salar). Fish were distributed into three vaccination groups (injectable, oral high dose, oral low dose). Feed intake and fish growth were recorded during the trial. The P. salmonis-specific IgM levels in blood plasma were measured by ELISA. Alginate microparticles containing the antigen were effectively incorporated in fish feed to produce the oral vaccine. Incorporation of AEPSA did not affect the palatability of the feed or the fish appetite. Furthermore, the oral vaccine did not have a negative effect on fish growth. Finally, the oral vaccine (high and low dose) produced an acquired immune response (IgM) similar to the injectable vaccine, generating a statistically significant increase in the IgM levels at 840-degree days for both experimental groups. These findings suggest that AEPSA incorporated in the feed can be an effective alternative to boost the immune response in Atlantic salmon (S. salar).